Intelligence quotient, short-term memory and study habits as academic achievement predictors of elementary school: A follow-up study - Quilez-Robres, Alberto; González-Andrade, Alejandro; Ortega, Zaira; Santiago-Ramajo, Sandra (Studies in Educational Evaluation, 2021)
Few studies have explored the differential contribution of general intelligence, short-term memory and study habits has on academic achievement during elementary school, especially during a two-year follow-up. The aim of this study is to determine whether there is a relationship between intelligence quotient (IQ), short-term memory and study habits and their ability to predict the academic achievement of children in elementary school (74 pupils aged 8–9 years old). The instruments used are the General and Factorial Intelligence Test (GFI-3 revised), the Yuste Memory Test (MY), the Study Habits and Techniques Questionnaire (SHTQ) and the average score obtained in the final exams in both 3rd and 4th grade. IQ, short-term memory and study habits are significantly related to academic achievement. These variables can predict 56–59 % (p < .001) of the variability of academic achievement. The study concludes that IQ and study habits are two significant predictor variables of academic achievement.
Keywords: intelligence quotient; short-term memory; study habits; academic achievement; elementary school; Scopus; JCR